Optimization and kinetic analysis on the sulfuric acid – Catalyzed depolymerization of wheat straw. (20th September 2015) - Wu, Qian-Qian; Ma, Yu-Long; Chang, Xuan; Sun, Yong-Gang
Highlights: A kinetic model for the description of the depolymerization of wheat straw was obtained. This kinetic model can satisfactorily predict the products during depolymerization. This kinetic model can describe the depolymerization mechanism using sulfuric acid. The optimum condition for depolymerization was 3 wt% H2 SO4 at 130 °C for 75 min. The activation energy for xylose formation during depolymerization was 44.99 kJ/mol. Abstract: The objectives of this work were to optimize the experimental condition and to study the kinetic behavior of wheat straw depolymerization with sulfuric acid (2 wt%, 3 wt%, and 4 wt%) at different temperatures (120 °C, 130 °C, and 140 °C). The two-fraction kinetic model was obtained for the prediction of the generations of product and by-product during depolymerization. The kinetic parameters of the two-fraction model were analyzed using an Arrhenius-type equation. Applying the kinetic two-fraction model, the optimum condition for wheat straw depolymerization was 3 wt% H2 SO4 at 130 °C for 75 min, which yielded a high concentration of fermentable sugars (xylose 8.934 g/L, glucose 1.363 g/L, and arabinose 1.203 g/L) and low concentrations of microbial inhibitors (furfural 0.526 g/L and acetic acid 1.192 g/L). These results suggest that the model obtained in this study can satisfactorily describe the formation of degradation products and the depolymerization mechanism of wheat straw.